Analisis Respon Siswa terhadap Powerpoint Interaktif Materi Sistem Peredaran Darah Manusia Kelas VIII - Anduweni; Laili Fitri Yeni; Kurnia Ningsih (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research was conducted to find out how students responded to interactive PowerPoint media on the human circulatory system material in class VIII of Kristen Immanuel II Sungai Raya Middle School. The research method in this research is quantitative descriptive. The sample in this study was 10 students in class VIII of Immanuel II Sungai Raya Christian Middle School. The population in this study were all students of the Christian Immanuel II Sungai Raya Middle School. The technique used was a simple random sampling technique with a lottery system. Data collection techniques in this research include interviews, observation and questionnaires. The overall average percentage of student responses to interactive PowerPoint media was 85.68% in the very positive category. the cognitive aspect obtained an average of 85.83% in the very positive category, the affection aspect 85.42% in the very positive category, the conation aspect 85.63% in the very positive category, and the overall average was 86% in the very positive category.